(untitled) (Global Journal of Science Frontier Research, 2020)
Chemistry laid the foundations for a wide range of branches of science from physics to biology. Moreover, its basic algorithm, the chemical formula, can be said to underlie the construction of mathematical graphs and the quantum-mechanical description with their help (Richard Feynman) of the interaction of elementary particles. And Chemistry itself received a scientific justification from these sections of Physics. But when analyzing the NANO-scale missed by physics, it became clear that these justifications, which became dogmatic postulates, brought not only Physics itself, but also Chemistry to saturation in the approximation to the Truth. It was this saturation that led to various so-called anomalies. which, in fact, are simply going beyond the applicability of the models used. It primarily refers to the "understanding" of chemical bondsin fact, to the canonization of orbitals calculated based on the Schrödinger equation. But as was shown earlier, the Schrödinger equation itself describes not the ELEMENTARY case but the PRIMITIVE. i.e. non-invariant for all chemical elements. Therefore, confining himself to Pauling’s ersatz representations (which he abandoned later, but which were canonized) is a dead-end in the chemical construction of new materials.